Effects of surface states on salt-frost scaling resistance of cement concrete - Hui Zhang; Peiwei Gao; Youqiang Pan; Zhixiang Zhang (Case Studies in Construction Materials, 2019)
This study discussed influences of surface states of concrete on salt-frost durability. By using the Capillary suction of Deicing solution and Freeze-thaw test method(CDF), the effects of factors, such as solution saturation in capillary, surface property and load coupling were compared and analyzed. It is found that drying shrinkage exerts greater effects on salt-frost resistance of the concrete in comparison with solution saturation in capillary. According to the CDF test standard recommended by RILEM, the salt-frost test results of the surface formed with the partitions in the laboratory overestimate salt-frost resistance of the concrete in the actual situation. Scaled mass of the top surface of the molded concrete due to salt frost is about 50% larger than that of the surface formed with the partitions. Coupling effects of repeated load and salt-freezing cycles can aggravate salt-frost damages of the concrete. Keywords: Salt-freezing cycle, Saturation, Surface property, Load coupling